2018
DOI: 10.1037/dev0000514
|View full text |Cite|
|
Sign up to set email alerts
|

A cross-language study of decontextualized vocabulary comprehension in toddlerhood and kindergarten readiness.

Abstract: [Correction Notice: An Erratum for this article was reported in Vol 54(7) of (see record 2018-30226-001). In the article, the reference for Legacy, Zesiger, Friend,& Poulin-Dubois (2016) should be Legacy, Zesiger, Friend, & Poulin-Dubois (2018). The correct reference for the article is listed below: Legacy, J., Zesiger, P., Friend, M., & Poulin-Dubois, D. (2018). Vocabulary size and speed of word recognition in very young French-English bilinguals: A longitudinal study. Bilingualism: Language and Cognition, 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 81 publications
1
41
1
Order By: Relevance
“…Correct responses in picture pointing tasks have been shown to predict subsequent language outcomes and readiness for school (Friend, (in review), Smolak, Liu, Poulin-Dubois, & Zesiger, 2016). Therefore, children’s most robust word knowledge may be a stronger predictor of developmental outcomes than is partial knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Correct responses in picture pointing tasks have been shown to predict subsequent language outcomes and readiness for school (Friend, (in review), Smolak, Liu, Poulin-Dubois, & Zesiger, 2016). Therefore, children’s most robust word knowledge may be a stronger predictor of developmental outcomes than is partial knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…The French CCT has moderate test- retest reliability and convergent validity with the IFDC (Friend & Zesiger, 2011). Internal consistency is strong across forms (Cronbach’s α = .92 and .91, respectively; Friend, et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Decontextualized, in contrast to context-bound, associations may provide the substrate for subsequent word knowledge and conceptual development (Schmitt, 2014) and predict downstream language and cognitive ability. Friend, et al (2018) found that decontextualized vocabulary in the second year predicted vocabulary comprehension and kindergarten readiness at age four in monolingual English and French-speaking children and in bilingual children acquiring French and English simultaneously. Decontextualized vocabulary was a stronger predictor than parent report with effect sizes comparable to or greater than those in prior studies.…”
mentioning
confidence: 88%
“…Past studies show that reading texts through word incidental learning determined the ways in which readers interpret the meaning and the key term or words explanation, which supports the main idea that sentences increase the global inference (Pam and Karimi, 2016;Lee, 2017). Oxford (2002) and Friend et al (2018) reported that compound words or phrases contributed to memorization strategy development through semantic association. However, past studies investigated the effect of word incidental learning on students' VLS development under the level of compound words or phrases, and a few studies examined the word incidental learning effect on VLS development through a sentence-level explanation.…”
Section: Past Studies On Vls Developmentmentioning
confidence: 65%